Doing more than is necessary - Stingley, Caroline Scott (My University, 1891)
Introduction: Whenever for a while our thoughts turn upon self, what we are doing, and what we might do, we come to realize the fact that we are not doing as much as we might; that we have a tendency to indifference, to sluggishness, or to doing just what we have to and no more. The great majority of mankind will find this to be the case. Not, however that they let this hold them back in the world, but there is the tendency and it is to be overcome as it is by many many people; and it is to this class we wish to call your attention. Man’s first duty is to keep himself from the poor-house, from being a burden on society, to take care of himself soul, mind and body. And in one sense I mean by this that he is if possible, to get sick. Many good arguments are brought forward against this thing of getting rich, yet it is the duty of every person to do so if he can honorably. He is not to be content with having just enough to support himself and those dependent upon him, but is to have a surplus of something with which to help and thus help himself.
Citation: Stingley, Caroline Scott. Doing more than is necessary. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Poverty; Duty; Morals; Helping others; Philanthropy; Sociology; Theses; Manuscripts (documents)